Enhanced stability of nitrogen doped porous carbon fiber on cathode materials for high performance lithium–sulfur batteries. Issue 35 (16th August 2022) - Wu, Xi; Jie, Xiaohua; Liang, Xinghua; Li, Suo; Lan, Lingxiao; Xie, Dan; Liu, Yusi
Abstract : The conductive network of nitrogen-doped porous carbon nanofibers was successfully prepared by the template method. The doping of nitrogen and the synergistic effect of mesopores and micropores reduce the energy barrier of Li + migration in the material. Abstract : Lithium–sulfur (Li–S) batteries are considered to be one of the candidates for high-energy density storage systems due to their ultra-high theoretical specific capacity of 1675 mA h g −1 . However, problems of rapid capacity decay, sharp expansion in volume of the active material, and the shuttle effect have severely restricted their subsequent development and utilization. Herein, we design a nitrogen-doped porous carbon nanofiber (NPCNF) network as a sulfur host by the template method. The NPCNF shows a feather-like structure. After loading sulfur, the NPCNF/S composite can maintain a hierarchically porous structure. A high discharge capacity of 1301 mA h g −1 is delivered for the NPCNT/S composite at 0.1C. The reversible charge/discharge capacity at 2C is 576 mA h g −1, and 700 mA h g −1 is maintained after 500 cycles at 0.5C. The high electrochemical performance of this NPCNT/S composite is attributed to the synergy effects of abundant N active sites and high electrical conductivity of the material.